Body composition indices and tissue loss in patients with resectable gastric adenocarcinoma. Issue 1 (1st January 2017) - Aahlin, Eirik Kjus; Irino, Tomoyuki; Johns, Neil; Brismar, Torkel; Nilsson, Magnus; Revhaug, Arthur; Lassen, Kristoffer
Abstract: Background: Body composition analyses from computed tomography (CT) scans have been used to assess cachexia in cancer patients. We investigated body composition indices, tissue change and treatment outcome in patients with resectable gastric adenocarcinoma. Methods: A cohort analysis of all patients treated with curative intent for gastric adenocarcinoma in two Scandinavian university hospitals from 2008–2011 was performed (n=137). Body composition analyses were performed on CT images taken for routine diagnostics and staging. Both preoperative single scans and repeat CT examinations were analyzed. Results: Perioperative chemotherapy was given to 58 (42.3%) patients. Forty patients (29.2%) suffered severe postoperative complications and 70 (51.1%) patients died within three years. There was a significant reduction in patients' lean tissue during neoadjuvant chemotherapy (p=0.001). There was no association between skeletal muscle tissue index and postoperative complications. Poorer survival was observed in patients with preoperative skeletal muscle tissue index within the lowermost quartile, independent of tumor characteristics and neoadjuvant treatment (HR=1.91, 95% CI 1.11–3.28, p=0.019). Conclusions: Patients lost lean tissue during neoadjuvant treatment for gastric adenocarcinoma. Low preoperative skeletal muscle index was not associated with postoperative complications, but strongly associated with poorer survival.